Students' Perception Of Non-Native Japanese Speaker Teacher's Competencies (Nnjsts) : Gender-Based Review - Laksana, Ketut Gede Adi Putra; Tobing, Roswita Lumban (International Journal Labs, 2024)
Japanese is one of the foreign languages taught in formal and informal educational institutions in Indonesia. The development of Japanese language learners is increasing quantitatively. In foreign language courses, native and non-native teachers collaborate on pedagogical tasks. This trend is also happening in Japanese foreign language courses. In addition, there are around 6,617 non-native Japanese language teachers (Japan Foundation, 2021). There is an argument that Native Japanese Speaker Teacher's (NJST) has many advantages over Native Japanese Speaker Teacher's (NNJSTs) and that students prefer NNJSTs over NJST, but the argument must be assessed. Many researchers have explored students' perceptions of NJSTs and NNJSTs worldwide in formal education institutions but not in the non-formal education institution sector. This study aims to explore the perception of Indonesian students towards NNJSTs in non-formal educational institutions, namely LPK Fuji Academy Singaraja with all samples coming from active students registered from January to August 2024. This study is a quantitative research with a descriptive approach conducted using an instrument in the form of a closed questionnaire based on the Likert scale. This study revealed that the perception of male and female students did not have a significant difference in their teaching competence based on the theory of Nuibe et al (2006). Male participants rated NNJSTs higher in terms of teaching effectiveness and communication skills, with an average score of 9.8. In contrast, female respondents gave slightly lower ratings in these areas with an average of 7.1. Furthermore, through this research, students need NNJSTs more because they allow for a successful learning process because of effective learning strategies. In addition, NNJSTs also help students in facing difficulties and challenges in their learning process.